Josef Prkna Goes to Court: Labour-Disability Rights, Discourse, and Enforcement in Habsburg-Occupied Bosnia - Avakumovic-Pointon, Isabelle (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2026)
In the summer of 1899, a woodworker named Josef Prkna sued his employer, Peter Buttazzoni, in the Sarajevo Small Claims Court. Prkna claimed that, while he had been recovering from typhoid fever, Buttazzoni had unjustly withheld part of his sick pay. Applying a critical disability studies lens to Prkna’s story, this article argues that sick, injured, and disabled industrial labourers in Austro-Hungarian Bosnia considered themselves bearers of legally enforceable “labour-disability rights.” This conviction arose, not from legislation, but from a polycentric labour-disability rights discourse that maintained that debilitated workers were entitled to sick pay, free medical care, and/or monetary compensation. Bosnian workers frequently used petitions and lawsuits to enforce these rights. Surprisingly, the Austro-Hungarian government regularly affirmed workers’ labour-disability rights in principle, despite rejecting most claims on factual grounds. This challenges the assumption, common in Bosnian labour historiography, that workers lacked meaningful insurance rights prior to 1902. It also encourages disability historians to examine how disability rights can manifest in administrative practices, civil justice, and disabled people’s own rhetoric, even in contexts without formal disability rights legislation. Finally, this article demonstrates that critical disability studies–inflected microhistory is a powerful tool for reconstructing the lived experiences of disabled people in the past.